High-Speed Penetration Test and Numerical Simulation of Ceramic-Reactive Powder Concrete Composite Target - Xuezhi Wu; Huihui Zou; Gan Li; Yihao Cheng; Chunming Song (Shock and Vibration)
To study the protective performance of ceramic materials against the high-speed penetration of projectiles, seven ceramic-reactive powder concrete (C-RPC) composite targets were designed. Using a 100/30 mm two-stage light-gas gun, penetration tests were performed at 1.4–2.0 km/s. The results showed that the penetration depth of the C-RPC target body first increased and then decreased as the target speed increased, and the corresponding reverse penetration speed was between 1743.2 m/s and 1803.9 m/s. LS-DYNA software was used to perform a wide-speed numerical simulation study of a projectile’s high-speed penetration of the composite target, focusing on the analysis of the deformation, mass loss, passivation, and penetration depth of the projectile. Changes in the parameters were compared with the experimental results of a C-RPC penetration test, which together revealed the changes in the damaging effect of the missile’s high-speed penetration of the C-RPC composite target. It provided a damage analysis of the high-speed/super-high-speed penetration of the projectile, which provides a reference for targeted protection research.